Effect of Graphene-Gold Nanocomposites on the Photocatalytic Activity Of TiO\(_2\) - Chinh, Vu Duc; Nguyen, Thuy Van; Binh, Pham Thanh; Hien, Chu Thi Thu (Communications in Physics, 2020)
The synthesis of graphene (Gr) - gold (Au) nanoparticle (NP) composite was achieved using continuous ultraviolet wave exposure. The functional groups were investigated with FT-IR spectra. From the Raman spectra, D-band and G-band of graphene were identified. As a result, the uniform deposition of nanometer-sized Au NPs on the graphene sheets was observed from the field emission scanning electron microscope (FE-SEM) images. The photodegradation of methylene blue in aqueous solutions is studied using various photocatalysts, including neat TiO2, Gr/TiO2 and Gr-Au/TiO2 composites. The Gr weight ratio in this research is 2%. The Gr2%-Au0.1%/TiO2 composite had the highest photoactivity.